LITERACY OF GUINEAN STUDENTS IN RELATION TO OPINION WRITING BEFORE STARTING UNILAB - Leite Infau, Laurindo (Revista Gênero e Interdisciplinaridade, 2024)
This work investigates the experience of five Guinean students about opinion writing before starting the University of International Integration of Afro-Brazilian Lusofonia (UNILAB), this type of writing is requested in admission exam for the selection process for foreign students at UNILAB. Methodologically, the research is a case study with qualitative analysis. Two instruments were used for the initial data collection procedure: the interview and the writing of an opinion article. However, for this text, only the interview part was explored, the answer to two interview questions about the target audience’s knowledge and mastery of writing opinion articles before their arrival at UNILAB. The form of analysis was based on the thematic analysis founded by Minayo (2007). As a result, it is concluded that students have little mastery of producing opinionated genres, before arriving in Brazil, because writing practice is not recurrent during their secondary education in Guinea-Bissau.